Cleaved endocan acts as a biologic competitor of endocan in the control of ICAM‐1‐dependent leukocyte diapedesis. Issue 5 (9th April 2020) - Gaudet, Alexandre; Portier, Lucie; Mathieu, Daniel; Hureau, Maxence; Tsicopoulos, Anne; Lassalle, Philippe; De Freitas Caires, Nathalie
Abstract: Dysregulated leukocyte diapedesis is a major contributor to acute severe inflammatory states like sepsis and acute respiratory distress syndrome, which are common conditions in critically ill subjects. Endocan is a circulating proteoglycan that binds to the leukocyte integrin LFA‐1 and blocks its interaction with its endothelial ligand ICAM‐1, subsequently leading to the inhibition of leukocyte recruitment. Recent data have highlighted the hypothetic role of p14, endocan's major catabolite found in the bloodstream of septic patients, as a potential antagonist of endocan, thus participating in the regulation of acute inflammation. We hereby characterize the role of p14 as a biologic competitor of endocan, through assessment of its molecular interactions with LFA‐1, endocan, and ICAM‐1, as well as its effects on human leukocyte trafficking. Using immunodetection assay, we report that p14 can bind to LFA‐1, thus inhibiting the interaction between LFA‐1 and endocan, which in turn leads to the restoration of the ICAM‐1/LFA‐1 interaction. In primary human T cells trafficking assays, we underline the absence of effect of p14 on ICAM‐1‐dependent adhesion and migration, as well as on transendothelial migration. However, in those models, p14 reverses the antimigratory effect of endocan. To conclude, our study supports the hypothesis of an antagonistic role of p14 versus endocan in its effect on the LFA‐1/ICAM‐1‐dependent human leukocyte recruitment. Abstract : Molecular and cellular impacts of p14 on endocan's regulatory effects in the control of leukocyte recruitment